Peningkatan Aktivitas dan Hasil Belajar Fisika dengan Metode Praktikum - Kahar, Muhammad; Hasyim, Mutahharah; Yunus, M; Sulaeman, Sulaeman (Universitas Negeri Makassar, 2024)
Abstract. The study was conducted in two cycles, consisting of: planning, implementation, analysis, reflection. The first cycle is obtained, the students activity consider the teacher's explanation 57.14%, using the laboratory equipment of 22.86%. cooperation between students in the group 28.57%, asking questions11.43%, answering teachers questions 45.71%, expressed ideas 8.57%, draw conclusions 42.85%. make reporting 51.43%, punctuality 42.86%. Learning outcomes mean 66.60, highs 79.00, lows 53.00, classical completeness 57.14%. In the second cycle of the student activity increased to 94.28%. Using laboratory equipment 85.71%. cooperation between of students in the group 71.43%, asking the question 40%, answered questions teachers 82.86%, expressed the idea 28.57%, summed 80.00%. makereporting 97.15%, punctuality 85.71%, and learning outcomes mean of 77.80, 89.00 highs, lows 63.00 88.57% classical completeness.published work. Keywords: Learning Activities, Learning Outcomes, Practical Methods, Classroom Action Research